La police face aux outils numériques: stratégies, pratiques et communication policière sur Twitter lors des manifestations a Montreal - Tuzza, Simone (Canadian journal of criminology and criminal justice, 2018)
The use of the media by protesters during demonstrations affects the police force and its response. The new media force the police to update its crowd control strategy. The police's scope of concern reaches an unprecedented level of exchange, because of the digital dimension adding to the physical one; it now has to take both into account in its crowd management practices. What is [End Page 354] the attitude adopted by the Service de police de la Ville de Montréal (SPVM) with regard to the social media? What use does it make of the Twitter microblogging platform during demonstrations? In order to understand how the law enforcement agency uses the potential of this media and how it impacts its communications and practices, a database of 3,909 Twitter messages, dated between September 2012 and June 2015, was created. An analysis of the database shows that the SPVM seeks to establish a direct and egalitarian dialogue with the public, tries to open a specific communication channel with protesters and uses this new medium as a strategic tool.